Reawakening Dapcha: Bridging Past and Present for Better Future - Rushat Pradhan; Moon Singh Dongol (KEC Journal of Science and Engineering, 2025)
Dapcha, a historically rich yet underdeveloped town in Nepal, faces significant socio-economic and infrastructural challenges despite its cultural heritage. This research paper, examines the current scenario and existing conditions of Dapcha through a comprehensive analysis of its historical context, urban fabric, socio-economic dynamics, and architectural heritage. The study highlights issues such as deteriorating traditional structures, inadequate infrastructure, and declining cultural practices due to urban migration and modernization pressures. By identifying critical areas of concern, the paper aims to provide a foundation for sustainable revitalization strategies that balance cultural preservation with modern development. The findings serve as a guide for policymakers, urban planners, and architects striving to create a future where Dapcha’s historical essence coexists harmoniously with contemporary progress.